Exploring the benefits of using Enterprise 2.0 tools to facilitate collaboration during product development. (2015) - Evans, Richard David; Gao, James Xiaoyu; Martin, Nick; Simmonds, Clive
Enterprise globalisation and technological advancements have created many opportunities and challenges for manufacturing organisations, including inter alia the need to develop flexible work processes during product development activities. The purpose of this paper is to report on an investigative study conducted within a leading Aerospace and Defence Industry (ADI) organisation to highlight the potential benefits offered by Enterprise 2.0 technologies to facilitate employee collaboration during PD activities. Although participants demonstrated a high degree of familiarity with current social media sites and Web 2.0 tools, the research suggests that little use is being made of them within the organisation, with employees still relying heavily on traditional means of communication for project collaboration. Furthermore, this paper discusses the design and development of a groupware prototype which has been validated through a real-world project to verify the benefits on offer to ADI companies when using Web 2.0 technologies.